2019
DOI: 10.1002/mds.27884
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson's Disease: Glucocerebrosidase 1 Mutation Severity Is Associated with CSF Alpha‐Synuclein Profiles

Abstract: Background Mutations in the gene glucocerebrosidase (GBA1) are specifically associated with alpha‐synucleinopathies, namely, Parkinson's disease (PD) and dementia with Lewy bodies. As disease‐modifying treatment options such as alpha‐synuclein lowering compounds are under way, patient stratification according to alpha‐synuclein‐specific enrichment strategies, possibly reflected by cerebrospinal fluid (CSF) profiles, is a much needed prerequisite. Objective Are GBA1 mutations associated with a CSF alpha‐synucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 19 publications
3
41
0
Order By: Relevance
“…To date, only a few studies have attempted to delineate the phenotypic profile associated to specific mutation classes, showing earlier age at onset and a greater risk for dementia and other nonmotor symptoms in carriers of severe variants. 10,[18][19][20][21] In the present study, we further addressed this issue by dividing patients with GBA-PD into subgroups based on the variant type and attempted to profile the clinical features that recurred more frequently, or earlier in the disease course, within each subgroup. Severe GBA variants were characterized by younger onset and more severe progression as per the shorter time to develop balance disturbances and the higher risk of hallucinations and cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only a few studies have attempted to delineate the phenotypic profile associated to specific mutation classes, showing earlier age at onset and a greater risk for dementia and other nonmotor symptoms in carriers of severe variants. 10,[18][19][20][21] In the present study, we further addressed this issue by dividing patients with GBA-PD into subgroups based on the variant type and attempted to profile the clinical features that recurred more frequently, or earlier in the disease course, within each subgroup. Severe GBA variants were characterized by younger onset and more severe progression as per the shorter time to develop balance disturbances and the higher risk of hallucinations and cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Lerche et al (2020) showed reduced CSF levels of total alpha-synuclein in GBA-PD compared to iPD and controls. Moreover, in this study, GBA-PD subjects bearing a severe mutation showed lower CSF levels of total alpha-synuclein than GBA-PD with mild or risk variant mutations or iPD patients.…”
Section: Biochemical Markersmentioning
confidence: 99%
“…Indeed, we could show that PD GBA present with lower CSF levels of total alpha-synuclein compared to healthy controls and also compared to PD GBA_wild type . Importantly, PD GBA with severe variants show the lowest mean values ( Lerche et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%